(untitled) (Fisioterapia e Pesquisa, 2007)
The study aimed at evaluating the prevalence of delay in functional mobility among 1 to 4 year-old children with asthma, also describing socialdemographic factors associated to such prevalence. This cross-sectional study included 62 children with asthma who attended the program Criança que Chia at health centres in the city of Belo Horizonte, MG. Functional mobility was evaluated using the functional skills mobility scale from the Paediatric Evaluation of Disability Inventory. Fisher Exact test was used to assess the association between mobility delay and the variables sex and family's socioeconomic status; the T-test compared children mean ages with and without delay. A prevalence of 12.9 was found of delay in functional mobility among children with asthma (p=0,0001). No significant association was found between mobility delay and social-demographic variables (t=1,73; p=0,088). Results broaden information about the impact of asthma on child development, pointing that delay in mobility is an important factor to be considered in the care of children with asthma. It is suggested that motor assessment, aimed at early identification of delay, should be incorporated into the clinical repertoire of professionals who deal with these clients.